Prediagnostic prostate‐specific antigen kinetics and the risk of biopsy progression in active surveillance patients. (13th January 2016) - Iremashvili, Viacheslav; Barney, Shane L; Manoharan, Murugesan; Kava, Bruce R; Parekh, Dipen J; Punnen, Sanoj
Abstract : Objective: To analyze the association between prediagnostic prostate‐specific antigen kinetics and the risk of biopsy progression in prostate cancer patients on active surveillance, and to study the effect of prediagnostic prostate‐specific antigen values on the predictive performance of prostate‐specific antigen velocity and prostate‐specific antigen doubling time. Methods: The study included 137 active surveillance patients with two or more prediagnostic prostate‐specific antigen levels measured over a period of at least 3 months. Two sets of analyses were carried out. First, the association between prostate‐specific antigen kinetics calculated using only the prediagnostic prostate‐specific antigen values and the risk of biopsy progression was studied. Second, using the same cohort of patients, the predictive value of prostate‐specific antigen kinetics calculated using only post‐diagnostic prostate‐specific antigens and compared with that of prostate‐specific antigen kinetics based on both pre‐ and post‐diagnostic prostate‐specific antigen levels was analyzed. Results: Of 137 patients included in the analysis, 37 (27%) had biopsy progression over a median follow‐up period of 3.2 years. Prediagnostic prostate‐specific antigen velocity of more than 2 ng/mL/year and 3 ng/mL/year was statistically significantly associated with the risk of future biopsy progression. However, after adjustment for baseline prostate‐specific antigen density, these associations were no longer significant. None of the tested prostate‐specific antigen kinetics based on combined pre‐ and post‐diagnostic prostate‐specific antigen values were statistically significantly associated with the risk of biopsy progression. Conclusions: Historical prediagnostic prostate‐specific antigens seems to be not clinically useful in patients diagnosed with low‐risk prostate cancer on active surveillance.